Crystal structure and magnetism of rare earth intermetallic compound Dy0.33Ho0.33Er0.33Ni. Issue 1 (1st October 2022) - Mohapatra, Abhaya Prasada; Chelvane, J. Arout; Morozkin, A. V.; Ramaprabhu, S.; Nirmala, R.
Abstract : Multi-component rare earth intermetallic compound Dy0.33 Ho0.33 Er0.33 Ni has been prepared by arc melting and characterized by powder X-ray diffraction and magnetization experiments. The sample crystallizes in orthorhombic FeB-type structure at 300 K and ferromagnetically orders around 40 K (TC ). The TC is close to the average value of the ferromagnetic transition temperatures of DyNi, HoNi and ErNi compounds. Magnetization has been measured as a function of field up to 15 kOe and low field magnetocaloric effect around the magnetic transition temperature is computed.